2013
DOI: 10.1155/2013/502153
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study to Investigate the Role of Thymidylate Synthase as a Marker of Prognosis for Neoadjuvant Chemotherapy in Gastric and Gastro-Oesophageal Junction Adenocarcinoma

Abstract: Aims and Background. Patients in the United Kingdom with operable gastric and gastro-oesophageal junction (GOJ) tumours receive neoadjuvant chemotherapy. Our aim was to study the expression of thymidylate synthase (TS) enzyme in pre-treatment diagnostic biopsy specimens and investigate its clinical usefulness. Methods. A single-centre study was carried out in 45 patients with gastric and GOJ adenocarcinoma treated with neo-adjuvant chemotherapy according to the MAGIC protocol. TS expression was determined usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In contrast, CRC patients having high levels of TS had poorer survival compared to those with low TS levels (19, 20). Similarly, patients with TS negative tumors had a better outcome than those with TS positive tumors in gastric and gastro-esophageal adenocarcinoma (21). Gao et al (22) also showed a correlation of high TS expression with unfavorable survival and lower response rates to FU-based chemotherapy in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, CRC patients having high levels of TS had poorer survival compared to those with low TS levels (19, 20). Similarly, patients with TS negative tumors had a better outcome than those with TS positive tumors in gastric and gastro-esophageal adenocarcinoma (21). Gao et al (22) also showed a correlation of high TS expression with unfavorable survival and lower response rates to FU-based chemotherapy in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal pH range in leukemia is 7.0-8.1 [147]. TS is also a prognostic biomarker in tumors and is associated with drug resistanc [148][149][150][151][152][153].…”
Section: Dihydroorotase Inhibitorsmentioning
confidence: 99%
“…TS is also a prognostic biomarker in tumors and is associated with drug resistance [ 148 , 149 , 150 , 151 , 152 , 153 ].…”
Section: The Pyrimidine Synthesis Pathwaymentioning
confidence: 99%